(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Standardization of herbal formulations is a process of setting some standard parameters which are essential for assuring the quality of the herbal formulations and it should be reproducible at any time of stability period of that formulations. Today many people all over the world experiencing the side effects of Modern medicine are shifting towards the traditional medical systems, among them most widely accepted is Ayurveda. Increased demand of herbal medicines, along with disparity in demand and supply of raw materials and profit mindedness of pharmaceutical agencies, has resulted substandard and unsafe products. The adulteration and substitution of drugs, methods of collection, storage and preservation of raw drugs, controversial opinions regarding formulations in classical text books, addition of preservatives and improper purification of toxic herbal and mineral drugs are the main problems that leading to the production of substandard and unsafe products. Authorities like WHO and Govt. of India has taken steps to standardize the individual drugs and formulations. Ministry of AYUSH have given the standard parameters for different types of preparations and few of the individual formulations are standardized in Ayurvedic pharmacopoeia of India. As the general population uses Ayurvedic medicines mainly as polyherbal formulations, standardization of each formulations is a need of hour for ensuring the quality medicines that leading to the global acceptance of Ayurveda.